Consumers’ cultural attitude toward mobile advertising: An empirical investigation among different national cultures - Islam, Maidul; Kang, Mincheol (Journal of Theoretical and Applied Information Technology, 2019)
The aim of this study is to examine the relationships between the characteristics of advertisement and consumer attitude toward mobile advertisement. How national culture moderates those relationships. A survey was conducted with consumers from three different countries (Korea, India, and China). Results show that consumers are willing to accept mobile ads if they are informative, credible, and interactive. Results also indicate that the Power Distance Index (PDI) of national culture has positive moderating effects on the relationships of informativeness and credibility, with attitude toward mobile advertising and the Uncertainty Avoidance Index (UAI) of national culture having negative moderating effects on the interactivity of mobile ads.
Keywords: Consumer attitude; Cultural dimension; Hofstede; Mobile advertising; National culture